Effectiveness of Lavender (Lavandula angustifolia) and Jasmine (Jasminum officinale) Aromatherapy on the Intensity of Dysmenorrhea in Student of Faculty of Public Health, Universitas Nusa Cendana, Kupang - Nurak, Maria Antonia; Lerik, M. Dinah Charlota; Tibuludji, Paula; Muntasir, Muntasir; Refli, Refli (Journal of Maternal and Child Health, 2020)
Background: Dysmenorrhea is a menstrual cramp that in general occurs in adolescents. In In